Country heterogeneity and the missing tier in the SDGs reporting - Alsayyad, Amina Said (2019)
"Many countries have made significant strides in transitioning from the Millennium Development Goals (MDGs), which expired in 2015, to the Sustainable Development Goals (SDGs). The 17 interdependent SDGs cover social, economic and environmental development issues as well as governance and partnerships. Each goal has a list of targets that are measured with indicators". (...)